Advancing balancing machine technology: A cost-effective solution for laboratory and small-medium enterprises - Mohd Firdaus, Hassan; Syazani, Mohd Sanosi; Ja'afar, Othman; Mohd Shahrul Azmi, Mohamad Yusoff (Faculty Mechanical Engineering, UMP, 2023)
Small-medium enterprises (SMEs) that provide maintenance services to power plant companies, notably on rotor components, encounter a significant challenge in balancing. The main concern is the high cost associated with outsourcing balancing services. The absence of portable balancing machines requires transporting components back to the workshop, resulting in substantial downtime lasting weeks before reinstallation. This paper presents a DIY-compatible balancing machine design and its assembly process, which can be applied to various balancing processes. The design primarily emphasizes mechanical aspects, excluding measurement and instrumentation components, which can be obtained or developed based on the user's software proficiency. The actual expenditure for developing this balancing machine is approximately RM11,698.00. In the development process, benchmarking, concept scoring, functionality evaluations, dynamic analysis, and ideation for workable balancing machine concepts were all involved. The modal analysis demonstrates that the first natural frequency at 279.5 Hz (equivalent to 16,770 rpm) is significantly higher than the motor's excitation frequency, which reaches a maximum speed of around 2800 rpm (46.67 Hz). This result indicates that the dynamic behaviour of the balancing machine does not significantly affect the dynamic results of the rotor balancing process.